Beyond treatment: navigating existential reflections in the cancer survivorship journey - S., Ramya (International Journal Of Community Medicine And Public Health, 2024)
This narrative review explores the intricate intersection of cancer survivorship and existential reflections, acknowledging the profound impact on the overall well-being and quality of life for survivors. As advances in treatment increase survival rates, understanding the psychosocial aspects of survivorship becomes crucial. This review examines how existential concerns evolve through the phases of survivorship, focusing on themes such as fear of recurrence, reassessment of life priorities, and the quest for renewed purpose. It also investigates the influence of social support, cultural and spiritual beliefs, and mental health on these reflections. By evaluating existing support services and interventions, the review highlights successful strategies and identifies areas for improvement. Recommendations are proposed for integrating existential considerations into survivorship care, emphasizing the need for comprehensive, culturally sensitive support to enhance survivors' quality of life and foster resilience and personal growth.